2013
DOI: 10.1371/journal.pone.0073734
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 Duplication Linked to Intersex in Deer

Abstract: A complex network of genes determines sex in mammals. Here, we studied a European roe deer with an intersex phenotype that was consistent with a XY genotype with incomplete male-determination. Whole genome sequencing and quantitative real-time PCR analyses revealed a triple dose of the SOX9 gene, allowing insights into a new genetic defect in a wild animal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…In fact, duplications of SOX9 are associated with XX sex reversal not only in transgenic mice 9 but also in the recently reported case of a deer, 38 and in three cases of dogs. 39 Our case 3 shows that also interruption of the region upstream to the RevSex can result in XX sex reversal.…”
Section: Discussionmentioning
confidence: 81%
“…In fact, duplications of SOX9 are associated with XX sex reversal not only in transgenic mice 9 but also in the recently reported case of a deer, 38 and in three cases of dogs. 39 Our case 3 shows that also interruption of the region upstream to the RevSex can result in XX sex reversal.…”
Section: Discussionmentioning
confidence: 81%
“…Transgenic mouse studies have shown the crucial roles of Sox9 in testis development: ectopic expression in XX gonads induces testis formation [7] , whilst loss-of-function of the gene causes XY sex reversal, resulting in failure to form Sertoli cells [8] . Gonadal sex reversals caused by misexpression of SOX9 have also been reported in human and European roe deer ( Capreolus capreolus ) [9] , [10] , [11] , and this suggests that the roles of the gene in testis differentiation are widely shared in mammals.…”
Section: Introductionmentioning
confidence: 79%
“…A duplication adding a third copy could increase this basal expression level above the threshold needed for testis induction. Interestingly, a duplication of the entire SOX9 region including its regulatory domain was able to trigger XX female-to-male sex reversal in human, deer and dog 4 32 33. Benko and co-workers suggest the involvement of epigenetic packaging of the 78 kb RevSex region, which includes the XXSR, in the regulation of SOX9 expression 12.…”
Section: Discussionmentioning
confidence: 99%